Annual Plan 2012-13 Volume-I Planning Commission Government of Chhattisgarh - Planning Commission (Planning Commission, 2012)
Chhattisgarh, the 26 State of the Union of India is situated between 17° 46' N to 24° 5'N latitudes and 80° 15’E to 84° 20' E longitudes. the total geographical area of the State is 1,37,898 sq km of which 43.34% area falls under reserved and protected forests. Another 13.15% percent geographical area is covered by revenue forests. Cultivable area is 34% of the total geographical area. the State is surrounded by six States, namely Madhya Pradesh, Maharashtra, Andhra Pradesh, Orissa, Jharkhand, and Uttar Pradesh. State is divided in to 27 revenue districts, and 146 developmental blocks of which 85 are tribal blocks located in Schedule Five areas.
Government of Chhattisgarh State Planning Commission